2011
DOI: 10.1104/pp.111.188615
|View full text |Cite
|
Sign up to set email alerts
|

Gravistimulation Changes the Accumulation Pattern of the CsPIN1 Auxin Efflux Facilitator in the Endodermis of the Transition Zone in Cucumber Seedlings  

Abstract: Cucumber (Cucumis sativus) seedlings grown in a horizontal position develop a specialized protuberance (or peg) on the lower side of the transition zone between the hypocotyl and the root. This occurs by suppressing peg formation on the upper side via a decrease in auxin resulting from a gravitational response. However, the gravity-stimulated mechanism of inducing asymmetric auxin distribution in the transition zone is poorly understood. The gravity-sensing tissue responsible for regulating auxin distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 39 publications
(70 reference statements)
0
20
0
Order By: Relevance
“… 54 and Watanabe et al . 55 . Excised root tips were immediately fixed in 4% 1-ethyl-3-(dimethylaminopropyl)-carbodiimide hydrochloride (EDAC) and 4% paraformaldehyde for 24 h at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“… 54 and Watanabe et al . 55 . Excised root tips were immediately fixed in 4% 1-ethyl-3-(dimethylaminopropyl)-carbodiimide hydrochloride (EDAC) and 4% paraformaldehyde for 24 h at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…6 This result suggested that the pronounced auxin efflux due to CsPIN1 causes a decrease in auxin level in the upper side of the transition zone. 6 Here our spaceflight study demonstrate that CsPIN1 re-localization is a graviresponse, which could results in auxin redistribution in the transition zone of cucumber seedlings.…”
Section: Discussionmentioning
confidence: 94%
“…6 We conducted spaceflight experiments on the International Space Station (ISS) to investigate the effects of gravistimulation on CsPIN1 localization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In gravistimulated roots, auxin redistribution is thus established, and transcriptional regulation depending on the auxin level on the upper and lower sides leads to downward bending. Spaceflight experiments with cucumber seedlings in the Space Shuttle and the International Space Station (ISS) showed that the endodermal cells relocalize an auxin efflux carrier, CsPIN1, because of gravistimualtion in space and laterally transport auxin from the upper to lower flank [17][18][19] . Some factors that could be involved in PIN polarization and thereby asymmetric auxin flow have been reported.…”
Section: Gravity Sensing In Plants Auxin Regulation Of Gravimorphogenmentioning
confidence: 99%